Integration of Madrasah Diniyah Al-Furqon with Formal Education in Developing Students Religious Character in the Disruption Era - Nurdianzah, Erry; Ma'arif, Syamsul; Junaedi, Mahfud (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2024)
Religious character education is a serious challenge for formal educational institutions in Indonesia, especially when facing an era of disruption that has seen educational institutions digitized. Various efforts have been made, including integrating formal educational institutions with madrasah diniyah to strive for the development of students' religious character. Based on this, this research aims to examine education in madrasah diniyah, the integration model between madrasah diniyah and formal educational institutions, and the results of this integration. This research is qualitative, using a case study approach. This research was conducted at three educational institutions, namely Madrasah Diniyah Al-Furqon, MI Al-Furqon, and SDN 3 Panjang. The results of the research show that religious education at Madrasah Diniyah Al-Furqon has built a religious foundation and also the religious character of students. From this, institutional integration has been formed between Madrasah Diniyah Al-Furqon and MI Al-Furqon and cultural integration between Madrasah Diniyah Al-Furqon and SDN 3 Panjang. This integration makes students have deeper values: social awareness, discipline, worship, politeness, and also Islamic knowledge are greater than students who do not study at madrasah diniyah.